Combining Diagnostic Imaging and Pathology for Improving Diagnosis and Prognosis of Cancer. (1st July 2019) - Schillaci, Orazio; Scimeca, Manuel; Toschi, Nicola; Bonfiglio, Rita; Urbano, Nicoletta; Bonanno, Elena
Abstract : In the era of personalized medicine, the management of oncological patients requires a translational and multidisciplinary approach. During early phases of cancer development, biochemical alterations of cell metabolism occur much before the formation of detectable tumour masses. Current molecular imaging techniques, targeted to the study of molecular kinetics, employ molecular tracers capable of detecting cancer lesions with both high sensitivity and specificity while also providing essential information for both prognosis and therapy. On the contrary, complementary and crucial information is provided by histopathological examination and ancillary techniques such as immunohistochemistry. Thus, the successful collaboration between diagnostic imaging and anatomic pathology can represent a fundamental step in the "tortuous" but decisive path towards personalized medicine.